A participação de respostas de autodiscriminação em classes de estímulos equivalentes - Queiroz, Anna Beatriz Müller (2007)
The purpose of this study was: (1) to establish the control of two (typing) responses as SD or conditional stimuli over a second response of choice between stimuli in a MTS task, (2) to verify if the typing responses became members of equivalent stimulus classes, and (3) if other stimuli of the equivalent classes would have discriminative functions similar to these responses . Seven adults participated in the study. On Phase 1 subjects were trained in a MTS task (stimuli relations AB and BC), then tested for the emergence of two stimulus equivalence classes (1 and 2) with three arbitrary stimulus in each one. On Phase 2 typing RFV or UJM on a computer became the stimuli controlling the choice of stimuli B1 or B2. On Phase 3 it was tested if (a) the typing responses became members of the equivalence classes established on Phase 1 and (b) if stimuli (C1 and C2) which had not been present on Phase 2 - acquired discriminative functions similar to the typing responses. Results showed that: equivalence classes were established for all participants on Phase 1; the typing responses assumed discriminative/ conditional functions, controlling the choice between two arbitrary stimuli on Phase 2; the typing responses became members of the equivalence classes; and members of the equivalence classes not present on Phase 2 assumed discriminative functions. Discussion highlights these findings and the consistency of the results